Handbook of air conditioning and refrigeration - Shan K. Wang (McGraw Hill, 1994)
* A broad range of disciplines--energy conservation and air quality issues, construction and design, and the manufacture of temperature-sensitive products and materials--is covered in this comprehensive handbook